Mobile Application for the Management of Covid-19 Health Measures on Public Transport Lines - Cabanillas-Carbonell, Michael (2022)
The pandemic is currently forcing several countries to take certain restrictions on public transportation to prevent the spread of the virus, Peru is in the aforementioned phase, so many users who continue to use public transportation on a daily basis to get to work, home, supermarkets, among other activities, must stay informed to comply with these requirements. In this context, the mobile application was developed to help the proper management of information of the sanitary measures of the Covid-19 in the area of public transport for the city of Lima, and this is compatible with Android and iOS; likewise, the Mobile-D methodology, helped to make such mobile application and to know the phases to proceed with the implementation, which has an impact on time, information management and user satisfaction. The results of the present document show that the level of user satisfaction increased to 67.5% of a sample of 200 people as the experimental group. It was concluded that the application made it possible to automate the management of information on Covid-19 sanitary measures in the field of public transportation.